Growing Entrepreneurial Spirit through the Practice of Making Pastries in Polonia Village, Medan Polonia District - Safrin, Feby Aulia; Mardhiyah, Ainun; Nasution, Beti (Talenta Publisher, 2023)
Indonesia as a developing country faces various problems that are usually faced by other developing countries, such as low income per capita of the population, high number of job seekers, limited job opportunities and economic and social conditions that are still lagging behind when compared to developed countries. Women have contributed to increasing the number of entrepreneurs. and advance this nation. Empowerment of women carried out in social development should be an empowerment that encourages women's awareness of their potential and abilities. The increasingly difficult economic development requires the participation of women or housewives to help support the household economy. Not only taking care of household domestic needs but women must increase their participation. Entrepreneurship is an option that housewives can do without leaving their role. The objectives of this community service activity are: (1) To provide a deeper understanding of the importance of entrepreneurship, especially for housewives in Polonia, Kec. Medan Polonia, (2) To see how much interest the housewives in Polonia Kec. Medan Polonia for entrepreneurship, (3) To provide insight on how to see business opportunities for housewives in Polonia, Kec. Polonia Field.